Analisis faktor-faktor yang berhubungan dengan partisipasi keluarga berencana di daerah rawan bencana - Musdalifah, Musdalifah; Olvaningsih, Olvaningsih (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Family planning (FP) participation is a crucial component in improving reproductive health and family well-being. However, in disaster-prone areas, FP participation often faces challenges due to changing social and emotional conditions and access to health services. This situation requires a deeper understanding of the factors influencing the involvement of couples of childbearing age (PUS) in FP programs. Purpose: To analyze factors related to family planning participation in disaster-prone areas. Method: The study employed a descriptive quantitative design with a cross-sectional approach to a sample of 74 PUS selected using the Slovin formula and proportionate stratified random sampling techniques, then reinforced with purposive sampling based on inclusion and exclusion criteria. Data were collected using a standardized questionnaire that had been tested for validity and reliability. Analysis was performed using the Chi-Square test with a significance level of 0.05. Results: Most respondents were of productive age and had at least a high school education, with a family planning participation rate of 74.3%. All tested variables had a significant relationship with family planning participation, including knowledge (p=0.001), self-efficacy (p=0.026), access to family planning services (p=0.017), and husband/family support (p=0.000). Family support was the strongest factor influencing active contraceptive use. Conclusion: Family planning participation in disaster-prone areas is significantly influenced by knowledge, self-confidence, ease of access, and family support.   Keywords: Disaster-Prone Areas; Family Planning Participation; Fertile Age Couples.   Pendahuluan: Partisipasi keluarga berencana (KB) merupakan komponen penting dalam meningkatkan kesehatan reproduksi dan kesejahteraan keluarga. Namun, di daerah rawan bencana, partisipasi KB sering menghadapi tantangan akibat perubahan kondisi sosial, emosional, dan akses pelayanan kesehatan. Kondisi ini menuntut pemahaman yang lebih mendalam mengenai faktor-faktor yang memengaruhi keterlibatan Pasangan Usia Subur (PUS) dalam program KB. Tujuan: Untuk menganalisis faktor-faktor yang berhubungan dengan partisipasi keluarga berencana di daerah rawan bencana. Metode: Penelitian menggunakan desain kuantitatif deskriptif dengan pendekatan cross sectional kepada sampel sebanyak 74 PUS yang dipilih menggunakan rumus Slovin dan teknik proportionate stratified random sampling, kemudian dipertegas dengan purposive sampling berdasarkan kriteria inklusi dan eksklusi. Data dikumpulkan menggunakan kuesioner terstandar yang telah diuji validitas dan reliabilitasnya. Analisis dilakukan menggunakan uji Chi-Square dengan tingkat signifikansi 0.05. Hasil: Sebagian besar responden berada pada usia produktif dan berpendidikan minimal SMA dengan tingkat partisipasi KB mencapai 74.3%. Seluruh variabel yang diuji memiliki hubungan bermakna dengan partisipasi KB yaitu pengetahuan (p=0.001), self-efficacy (p=0.026), akses layanan KB (p=0.017), dan dukungan suami/keluarga (p=0.000). Dukungan keluarga merupakan faktor paling kuat yang memengaruhi keaktifan penggunaan kontrasepsi. Simpulan: Family planning participation in disaster-prone areas is significantly influenced by knowledge, self-confidence, ease of access, and family support.   Kata Kunci : Daerah Rawan Bencana; Partisipasi Keluarga Berencana; Pasangan Usia Subur.